EVALUATION OF CONTROLLED RELEASE FORMULATIONS - ESTIMATION OF THE DURATION OF THE ZERO-ORDER ABSORPTION AND ASCERTAINMENT OF ABSORPTION KINETICS - Macheras, P. (BIOPHARMACEUTICS & DRUG DISPOSITION, 1991)
A compartmental approach for estimating the duration of the zero-order absorption was developed. For drugs obeying one-compartment model disposition, the estimation is based on an explicit relationship while an iterative process is required for drugs represented by two-compartment kinetics. A method based on a double graphical plot for ascertaining absorption kinetics for drugs exhibiting one-compartment model disposition was also developed.
Keywords: absorption kinetics; controlled release; Estimation; ZERO-ORDER ABSORPTION